Pengaruh Self-Hypnosis Therapy with Positive Self-Talk terhadap Tingkat Stres pada Pasien Diabetes Melitus - Chandranita Shailendra, Sagung; Candra, I Wayan; Ari Kresna Dewi, Ni Luh Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Diabetes mellitus is a major health problem that has reached an alarming level and endangers health. Patients with diabetes mellitus experience various physiological and psychological problems, one of which is stress. The stress condition of diabetes mellitus patients that is not treated can worsen their condition so that stress management is needed, self-hypnosis therapy with positive self-talk. The purpose of this study was to determine the effect of self-hypnosis therapy with positive self-talk on the stress level of diabetes mellitus patients in the Working Area of Puskesmas II West Denpasar in 2023. This type of pre-experimental research was with a one-group pre-post test design. The sampling technique used purposive sampling with a total of 30 research subjects. The research instrument uses the Perceived StressScale-10. The results showed that before being given self-hypnosis therapy with positive self-talk, 9 people (30.0%) had mild stress, 18 people (60.0%) had moderate stress and 3 people had severe stress (10.0%). After treatment, stress levels decreased, namely 17 people (56.7%) had mild stress and 13 people (43.3%) had moderate stress. There is an effect (p=0.00) of Self-Hypnosis Therapy With Positive Self-Talk on stress levels in diabetes mellitus patients in the Working Area of Puskesmas II Denpasar Barat in 2023. Self-Hypnosis Therapy With Positive Self-Talk can reduce stress levels in diabetic mellitus patientsScale-10. The results showed that before being given self-hypnosis therapy with positive self-talk, 9 people (30.0%) had mild stress, 18 people (60.0%) had moderate stress and 3 people had severe stress (10.0%). After treatment, stress levels decreased, namely 17 people (56.7%) had mild stress and 13 people (43.3%) had moderate stress. There is an effect (p=0.00) of Self-Hypnosis Therapy With Positive Self-Talk on stress levels in diabetes mellitus patients in the Working Area of Puskesmas II Denpasar Barat in 2023. Self-Hypnosis Therapy With Positive Self-Talk can reduce stress levels indiabetic mellitus patients.